Rukun Iman dalam Pembelajaran Aqidah Akhlak - Ira Suryani; Hasan Ma’tsum; Nora Santi; Murali Manik (Medan Resource Center, 2021)
Faith is one of the important points that must be attached to every Muslim, it is not enough for a person to be only Islam but there is no faith attached to him. Faith is meant to believe in the existence of Allah SWT, angels, messengers, books, the last day and good luck and bad luck. Good in heart, word and deed. Regarding faith in Allah, it is not strange that as Muslims we are required to be able to learn and understand what faith in Allah means. In writing this paper, we will try to describe the meaning of faith in Allah, as well as how the omniscience of Allah that we have always believed is the nature of Allah SWT. I think it is not enough just a lip statement about the oneness or attributes of Allah.